A study on abandoned housing projects in Selangor / Hijaratul Alif Manap - Alif Manap, Hijaratul (Faculty of Architecture, Planning and Surveying, 2013)
The housing industry in Malaysia is an important industry nowadays. However the present of abandoned housing projects was effect the housing industry in Malaysia. According to the Ministry of Housing and Local Governments (KPKT) records since 1990 till 2005, the problem of abandoned housing projects is indeed serious. It also recorded 261 projects involving 88,410 houses in Peninsular Malaysia were abandoned and 58,685 total of buyers were affected by this problems. Aim of this research is to study the abandoned housing projects in Selangor. Selangor was show the number of abandoned housing projects, which is 63 projects involving 32,987 houses affecting 22,480 buyers. The objective of the study is to know the causes of the abandoned housing projects and other factors influenced, to identify the impacts of abandoned housing projects and to recommend the method of prevention for housing project being abandoned. This research gets references from literature review and distribution of questionnaire to the selected respondents which have experience in the construction projects. The question asked in the questionnaire includes the general factors and others factors of abandoned housing projects and the impacts of abandoned housing projects. The data is analyzed and summarize by using chart. From the finding indicate the main factors of abandoned housing projects is poor construction and financial management by developer, the others main for general factors are unsuitable site location and the main impacts of abandoned housing projects are buyers are burdened with house loan while their house still abandoned. In this study also recommend the method of prevention for abandoned housing projects.